Association between Polymorphisms in MicroRNAs and Risk of Urological Cancer: A Meta-Analysis Based on 17,019 Subjects - Wang, Yu-Hui; Hu, Han-Ning; Weng, Hong; Chen, Hao; Luo, Chang-Liang; Ji, Jia; Yin, Chang-Qing; Yuan, Chun-Hui; Wang, Fu-Bing (Frontiers in Physiology, 2017)
Accumulating evidence has demonstrated that some single nucleotide polymorphisms (SNPs) existing in miRNAs correlate with the susceptibility to urological cancers. However, a clear consensus still not reached due to the limited statistical power in individual study. Thus, we concluded a meta-analysis to systematically evaluate the association between microRNA SNPs and urological cancer risk. Eligible studies were collected from PubMed, Embase, Web of Science, and CNKI databases. Pooled odds ratio (OR) and corresponding 95% confidence interval (95% CI) were calculated to assess the strength of the relationships between three SNPs (miR-196a2, C>T rs11614913; miR-146a, G>C rs2910164; and miR-499, A>G rs3746444) and the risk of urological cancers. In addition, the stability of our analysis was evaluated by publication bias, sensitivity and heterogeneity analysis. Overall, a total of 17,019 subjects from 14 studies were included in this meta-analysis. We found that CT (miR-196a2, C>T rs11614913) was a risk factor for renal cell carcinoma (CT vs. CC: OR=1.72, 95%CI=1.05-2.80, P=0.03, I2=66%), especially in Asian population (CT vs. CC: OR=1.17, 95%CI=1.04-1.32, P<0.01, I2= 0%). miR-146a G>C rs2910164 was a protective factor of urological cancers (C vs. G: OR=0.87, 95%CI=0.81-0.93, P<0.01, I2=0%), especially for bladder cancer. miR-499 A>G rs3746444 was correlated with an increased risk of urological cancers, specifically in Asian population. In conclusion, our meta-analysis suggests that polymorphisms in microRNAs, miR-196a2, C>T rs11614913, miR-146a G>C rs2910164 and miR-499 A>G rs3746444, may be associated with the development of urological cancers and the risks mainly exist in Asian populations.